Spatial Distribution and Seasonal Variation of Arsenic in Groundwater of the Kathmandu Valley, Nepal - Shrestha, S.M.; Rijal, K.; Pokhrel, M.R. (Journal of Institute of Science and Technology, 2015)
A study was conducted in forty-one deep groundwater and twenty shallow groundwater wells of Kathmandu Valley, Nepal to assess arsenic contamination (shallow and deep groundwater) and spatial and seasonal variation in deep groundwater. The depths of the wells were ranged from 9 to 304 m. Groundwater samples were collected during pre monsoon and post monsoon in 2012. Atomic Absorption Spectrometer (AAS) was used to measure the concentration of arsenic. In pre monsoon and post monsoon, 36.59 % and 31.70 % of deep groundwater wells, respectively exceeded permissible values of World Health Organization guideline value of 0.01 mg/L for drinking water. The arsenic varied spatially with high concentration towards central groundwater district. Negative correlation between arsenic and ORP showed reductive arsenic mobilization mechanisms in deep groundwater. There was very weak negative correlation between arsenic concentration and depth of deep groundwater wells. The t-test revealed that there is significant difference in concentration of arsenic in between shallow and deep ground water with higher values of arsenic in deep groundwater. Journal of Institute of Science and Technology, 2014, 19(2): 7-13